How Valid are Web-Based Self-Reports of Weight? - Bonn, Stephanie Erika; Trolle Lagerros, Ylva; Bälter, Katarina (JMIR Publications, 2013)
BackgroundMany studies rely on self-reported anthropometric data. While paper-based self-reports have been the standard collection mode, the number of studies collecting self-reported data via the Web is increasing rapidly. Although numerous studies have shown good agreement between self-reported and measured weight using paper-based questionnaires, the validity of using the Web to inquire about weight is unknown. ObjectiveThe objective of this study was to validate Web-based self-reports of bodyweight compared to weight measured at the study center. MethodsThe validity of weight self-reported via the Web was assessed by comparing self-reports against measurements of weight in a convenience sample of 149 individuals (77.2% women, 115/149), aged 20-65 years. Study participants self-reported their weight via a Web-based questionnaire and thereafter had their weight measured in the research center. ResultsThe Spearman correlation coefficient between self-reported and measured weight was 0.98 (P<.001). The mean difference between self-reported and measured weight was -1.2 (SD 2.6) kg. There was a statistically significant difference between self-reported and measured weight with the self-reported being lower (P<.001). Subjects with a body mass index (BMI) ≥25 kg/m2, and subjects ≥30 years of age, under-reported their weight statistically significantly more than subjects with a BMI <25 kg/m2, and subjects <30 years of age, respectively. ConclusionsOur results show that self-reported weight via the Web can be a valid method of data collection.